Vasculogenesis and Diabetic Erectile Dysfunction: How Relevant Is Glycemic Control?. Issue 1 (13th June 2016) - Castela, Angela; Gomes, Pedro; Silvestre, Ricardo; Guardão, Luísa; Leite, Liliana; Chilro, Rui; Rodrigues, Ilda; Vendeira, Pedro; Virag, Ronald; Costa, Carla
ABSTRACT: Erectile dysfunction (ED) is a complication of diabetes, condition responsible for causing endothelial dysfunction (EDys) and hampering repair mechanisms. However, scarce information is available linking vasculogenesis mediated by Endothelial Progenitor Cells (EPCs) and diabetes‐associated ED. Furthermore, it remains to be elucidated if glycemic control plays a role on EPCs functions, EPCs modulators, and penile vascular health. We evaluated the effects of diabetes and insulin therapy on bone marrow (BM) and circulating EPCs, testosterone, and systemic/penile Stromal Derived Factor‐1 alpha (SDF‐1α) expression. Male Wistar rats were divided into groups: age‐matched controls, 8‐weeks streptozotocin‐induced type 1 diabetics, and insulin‐treated 8‐weeks diabetics. EPCs were identified by flow cytometry for CD34/CD133/VEGFR2/CXCR4 antigens. Systemic SDF‐1α and testosterone levels were evaluated by ELISA. Penile SDF‐1α protein expression was assessed, in experimental and human diabetic cavernosal samples, by immunohistochemical techniques. Diabetic animals presented a reduction of BM‐derived EPCs and an increase in putative circulating endothelial cells (CECs) sloughed from vessels wall. These alterations were rescued by insulin therapy. In addition, glycemic control promoted an increase in systemic testosterone and SDF‐1α levels, which were significantly decreased in animals with diabetes. SDF‐1α protein expression was reduced in experimental and human cavernosal diabetic samples, an effect prevented by insulin in treated animals. Insulin administration rescued the effects of diabetes on BM function, CECs levels, testosterone, and plasmatic/penile SDF‐1α protein expression. This emphasizes the importance of glycemic control in the prevention of diabetes‐induced systemic and penile EDys, by the amelioration of endothelial damage, and increase in protective pathways. J. Cell. Biochem. 118: 82–91, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Insulin administration rescued diabetes effect in endothelial damage markers. Insulin therapy improves systemic and cavernosal protective protein and pathways. Glycemic control relevance in preventing diabetic penile endothelial dysfunction.